Giant angioleiomyoma of uterus masquerading as ovarian tumour: a case report - Bhandari, Purnima; Humane, Anil C.; Deshmukh, Vaishali S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Angioleiomyoma is a rare benign tumour of uterus. We are presenting an unusual case of 45-year-old female with 11 kg giant angioleiomyoma of uterus which was masquerading as ovarian tumour on imaging. Exploratory laparotomy was done which was suggestive of huge lobulated mass arising from the uterus. Hysterectomy with bilateral salpingo-oophorectomy was done. Histopathological examination of specimen was suggestive of uterine subserosal and broad ligament angioleiomyoma of cavernous type. This case is being reported because of its rarity and challenges in diagnosis and management.